Rapid Improvements in Itch with Tapinarof Cream 1% Once Daily in Two Phase 3 Trials in Adults with Mild to Severe Plaque Psoriasis - Leon Kircik; Matthew Zirwas; Shawn G. Kwatra; G. Michael Lewitt; Holly Glover; Tomas Chao; Philip M. Brown; David S. Rubenstein; Anna M. Tallman (Dermatology and Therapy, 2023)
Abstract Introduction Patients with psoriasis report pruritus as their most bothersome symptom. Tapinarof cream 1% once daily demonstrated significant efficacy versus vehicle and was well tolerated in adults with mild to severe plaque psoriasis in two 12-week trials: PSOARING 1 (NCT03956355) and PSOARING 2 (NCT03983980). Here, we present patient-reported pruritus outcomes from these trials. Methods Outcomes included a Peak Pruritus Numerical Rating Scale (PP-NRS) score of 0 or 1 (itch-free state); Dermatology Life Quality Index (DLQI) itch item scores; and Psoriasis Symptom Diary (PSD) itch item scores. Results Analyses included 683 tapinarof- and 342 vehicle-treated patients. At baseline, mean pruritus scores were similar across trials with only 7–11% of patients reporting an itch-free state. At week 12, the proportion of tapinarof-treated patients achieving an itch-free state was 50% in both trials compared with 32% (P = 0.0007) and 27% (P < 0.0001) in the vehicle groups. Improvements were apparent at the earliest assessments with continued improvement over the course of the trials. There were rapid and statistically significant improvements in the proportion of patients with a ≥ 4-point improvement in PP-NRS for tapinarof-treated patients versus vehicle from week 2 with 68% vs 46% (P = 0.0004) and 60% vs 31% (P = 0.0001) at week 12 achieving a response in each trial. Significantly greater reductions in itch with tapinarof versus vehicle were also demonstrated at week 12 for DLQI itch item 1 (P = 0.0026 and P < 0.0001), PSD item 1 (both P < 0.0001), and PSD item 2 (both P < 0.0001). Conclusion Tapinarof was highly efficacious in reducing pruritus across multiple patient-reported outcome measures, with rapid, statistically significant, and clinically meaningful improvements. The high proportion of patients achieving the treatment target of an itch-free state at week 12 (50%) is a noteworthy clinical outcome for a non-steroidal topical cream in the treatment of mild to severe plaque psoriasis. Trial Registration Clinical trial registration information: NCT03956355, NCT03983980.